Human Talent Management and its Impact on Organizational Commitment and Internal Communication in a Health Entity in Áncash - Gamonal Llatas, Maria Vilma (2024)
The objective of this research was to determine the level of incidence of human talent management in organisational commitment and internal communication of workers in a public health institution in Casma. The methodology used was applicative, non-experimental design, causal correlation of sectional scope, census sample of 184 workers. The survey was used and three questionnaires with reliability levels greater than 0.953 were used as instruments. It is concluded that human talent management, organisationalcommitment and internal communication show a regular level of 53.8%, 48.9% and 66.8% respectively. In addition, the results indicate a highly significant impact of human talent management on organisational commitment with Sig. P-value=0.000 < 0.01, the ordinal logistic regression using Nagelkerke's R2 with 0.761 which indicates that human talent management has an impact level of 76.10% on organisational commitment. On the other hand, there is a highly significant incidence of human talent management on internal communication with Sig. P-value=0.000 < 0.01, the ordinal logistic regression using Nagelkerke's R2 with 0.425 which refers that human talent management has an incidence level of 42.50% on internal communication.